Occurrence of Candida Species Colonization in a Population of Denture-Wearing Immigrants. (January 2013) - Calcaterra, R.; Pasquantonio, G.; Vitali, L.A.; Nicoletti, M.; Di Girolamo, M.; Mirisola, C.; Prenna, M.; Condò, R.; Baggi, L.
Infection of the oral cavity and dentures by Candida species are frequent in denture wearers. C. albicans is the most common pathogen; however, other emerging Candida species are also responsible for this condition. Few data are available about the occurrence of Candida species in the oral cavities of denture-wearing immigrants to Italy. In this study, we compare the Candida species found in the oral mucosa and on dentures from a population of denture wearing immigrants to Italy to a matched Italian group. Oral swabs were collected from dentures and the underlying mucosa of patients enrolled in the study and were then cultured to test for the presence of Candida species in each sample. Out of 168 patients enrolled (73 Italians and 95 immigrants), 51 Italians (69.8%) and 75 immigrants (78.9%) tested positive for the presence of Candida. Candida albicans was the most frequently observed species overall; however, we found a higher occurrence of C. glabrata among immigrants than among Italians. In addition, immigrants displayed a higher incidence of Candida – associated stomatitis and a lower mean age than Candida -positive individuals from the Italian group. Immigrants are more prone to longer colonization of the oral mucosa and dentures by Candida . In these patients, dentures must be checked periodically to prevent the presence of Candida .